The Effects of a “Health at Every Size®”-Based Approach in Obese Women: A Pilot-Trial of the “Health and Wellness in Obesity” Study - Ulian, Mariana Dimitrov; Benatti, Fabiana B.; de Campos-Ferraz, Patricia Lopes; Roble, Odilon J.; Unsain, Ramiro Fernandez; de Morais Sato, Priscila; Brito, Bruna Cristina; Murakawa, Karina Akemi; Modesto, Bruno T.; Aburad, Luiz; Bertuzzi, Rômulo; Lancha, Antonio H.; et al. (Frontiers in Nutrition, 2015)
This study explored the effects of Health at Every Size®-based intervention on obese women by qualitatively evaluating participants’ perception towards the program and quantitatively evaluating changes related to psychological, behavioral and body composition assessments. A prospective one-year quasi-experimental mixed-method trial was conducted. The mixed method design was characterized by a spiral method, and quantitative and qualitative findings were combined during the interpretation phase. The qualitative data involved three focus groups; and quantitative data comprised physiological, psychological and behavioral assessments. Initially, 30 participants were recruited; 14 concluded the intervention. From the focus groups, the following interpretative axes were constructed: the intervention as a period of discoveries; shifting parameters: psychological, physical and behavioral changes; eating changes, and; redefining success. Body weight, body mass index, total body fat mass and body fat percentage were significantly decreased after the intervention (-3.6, -3.2, -13.0, and -11.1%, respectively; p≤0.05, within-time effect). Participants reported being more physically active, and perceiving better their bodies. Eating-wise, participants reported that the hunger and satiety cues and the consumption of more frequent meals facilitated their eating changes. Finally, participants reported that they could identify feelings with eating choices and refrain from the restrained behavior. These qualitative improvements were accompanied by modest but significant improvements in quantitative assessments. Clinicaltrials.gov registration: NCT02102061.